2006
DOI: 10.1007/s11104-005-1545-8
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Variation of Soil Properties Relating to Vegetation Changes

Abstract: Bekele and Hudnall provide an interesting perspective on the spatial variation of soil chemical properties in a natural area undergoing transition from prairie to forest. Their focus is on the unique calcareous prairie ecosystem of Louisiana where prairie remnants are being encroached upon by the forest, primarily eastern red cedar (Juniperus virginiana L.). Bekele and Hudnall were especially interested in investigating any differences in spatial variability among similar sites and in documenting the scale at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 38 publications
0
17
0
1
Order By: Relevance
“…The results of the average test and C.V. indicate that there is no difference between the compartments studied. Some authors (SAUER et al, 2006) report that the average result is not a good analysis to be used to compare the compartments along the landscape. Other authors (SOUZA et al, 2007) reported that even inferring the variability by C.V., more detailed analysis are needed, using geostatistics to characterize the variability in different compartments of the landscape.…”
Section: Resultsmentioning
confidence: 99%
“…The results of the average test and C.V. indicate that there is no difference between the compartments studied. Some authors (SAUER et al, 2006) report that the average result is not a good analysis to be used to compare the compartments along the landscape. Other authors (SOUZA et al, 2007) reported that even inferring the variability by C.V., more detailed analysis are needed, using geostatistics to characterize the variability in different compartments of the landscape.…”
Section: Resultsmentioning
confidence: 99%
“…Kersic (1997) knew geo-statistics technique as the most confident, strongest and widest method for interpolation and has acknowledged that geo-statistics is the strategy that considers spatial variance, location and distribution of samples. Geo-statistics is a powerful tool for determining the spatial variability (Sauer et al, 2006). Geo-statistical methods use mathematical and statistical functions for interpolation and their basis is statistical characteristics of data.…”
Section: Introductionmentioning
confidence: 99%
“…The study area Sevapuri covers an area 16968 ha located at Rogerio et al, 2006Singh, 2012Hangsheng et al, 2005Wang et al, 2009Roberston et al, 1997Mishra Singh 2013, Kumari et al, 2013, 2014Pohlmann, 1993Sauer et al, 2006Pandey Mishra, 1991, Mishra Pandey, 1992 "UP-7 Eastern Plain Zone" agro climatic zone in Varanasi District (25°16'55.2″ north latitude and 82°5722.68″ east latitude) of Uttar Pradesh, India. The holy city Banaras lies in the middle Ganges valley of North India, in the Eastern part of the state of Uttar Pradesh (Fig.…”
Section: Methodsmentioning
confidence: 99%